Addressing harmful algal blooms (HABs) impacts with ferrate(VI): Simultaneous removal of algal cells and toxins for drinking water treatment. (November 2017) - Deng, Yang; Wu, Meiyin; Zhang, Huiqin; Zheng, Lei; Acosta, Yaritza; Hsu, Tsung-Ta D.
Abstract: Although ferrate(VI) has long been recognized as a multi-purpose treatment agent, previous investigations regarding ferrate(VI) for addressing harmful algal blooms (HABs) impacts in drinking water treatment only focused on a single HAB pollutant (e.g. algal cells or algal toxins). Moreover, the performance of ferrate(VI)-driven coagulation was poorly investigated in comparison with ferrate(VI) oxidation, though it has been widely acknowledged as a major ferrate(VI) treatment mechanism. We herein reported ferrate(VI) as an emerging agent for simultaneous and effective removal of algal cells and toxins in a simulated HAB-impacted water. Ferrate(VI)-driven oxidation enabled algal cell inactivation and toxin decomposition. Subsequently, Fe(III) from ferrate(VI) reduction initiated an in-situ coagulation for cell aggregation. Cell viability (initial 4.26 × 10 4 cells/mL at pH 5.5 and 5.16 × 10 4 cells/mL at pH 7.5) decreased to 0.0% at ≥ 7 mg/L Fe(VI) at pH 5.5 and 7.5, respectively. Cell density and turbidity were dramatically decreased at pH 5.5 once ferrate(VI) doses were beyond their respective threshold levels, which are defined as minimum effective iron doses (MEIDs). However, the particulate removal at pH 7.5 was poor, likely because the coagulation was principally driven by charge neutralization and a higher pH could not sufficiently lower the particle surface charge. Meanwhile, algal toxins (i.e., microcystins) of 3.98 μg/L could be substantially decomposed at either pH. And the greater degradation achieved at pH 5.5 was due to the higher reactivity of ferrate(VI) at the lower pH. This study represents the first step toward the ferrate(VI) application as a promising approach for addressing multiple HABs impacts for water treatment. Graphical abstract: Highlights: Fe(VI) can effectively inactivate algal cells and decompose microcystins. Fe(VI) can simultaneously initiate an in-situ Fe(III) coagulation to settle algal cells. Inactivation and oxidation efficiencies of Fe(VI) rely on pH and chemical dose. Fe(VI) coagulation is influenced by pH, highlighting a vital role of charge neutralization. Minimum effective iron doses (MEIDs) for turbidity are observed for Fe(VI) coagulation.